2006
DOI: 10.1007/s00442-006-0422-3
|View full text |Cite
|
Sign up to set email alerts
|

Solar ultraviolet-B radiation alters the attractiveness of Arabidopsis plants to diamondback moths (Plutella xylostella L.): impacts on oviposition and involvement of the jasmonic acid pathway

Abstract: Solar ultraviolet-B radiation (UV-B) can have large impacts on the interactions between plants and herbivorous insects. Several studies have documented effects of UV-B-induced changes in plant tissue quality on the feeding performance of insect larvae. In contrast, the effects of UV-B-induced plant responses on the behavior of adult insects have received little attention. We carried out a series of field and glasshouse experiments using the model plant Arabidopsis thaliana L. and the crucifer-specialist insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 48 publications
5
75
0
2
Order By: Relevance
“…This effect is not pronounced at the seed stage and was not detectable in our experiments during a window during germination, hypocotyl elongation, and cotyledon expansion that occurred before the appearance of the first leaves. These observations are consistent with the fact that light quality can strongly affect plant-insect interactions (23).…”
Section: Insects and Isopod Crustaceans Can Prey On Arabidopsis Seed supporting
confidence: 79%
“…This effect is not pronounced at the seed stage and was not detectable in our experiments during a window during germination, hypocotyl elongation, and cotyledon expansion that occurred before the appearance of the first leaves. These observations are consistent with the fact that light quality can strongly affect plant-insect interactions (23).…”
Section: Insects and Isopod Crustaceans Can Prey On Arabidopsis Seed supporting
confidence: 79%
“…Also as expected, npr1 and jar1 did not show an increase in HRF after MeSA or MeJA treatments, respectively, whereas jar1 responded with a relatively large increase in HRF in response to MeSA. Consistent with these data, jar1 plants were previously shown to be unable to establish a UV-B-induced protective response against herbivores (Caputo et al, 2006), suggesting a requirement for the jar1-encoded JA-amino acid conjugase in both response to pathogens and to abiotic stress-induced changes in HRF after exposure to UV light.…”
Section: Mesa and Meja Are Key Signaling Volatiles But Not The Only Osupporting
confidence: 73%
“…Moreover, UV-triggered changes in PR gene expression and activation of SA have been documented for several plant species (Green and Fluhr, 1995;Jenkins, 2009), and UV-induced transition to flowering has been found to be SA dependent (Martínez et al, 2004). Finally, UV exposure can activate defense mechanisms against insect herbivory in a JAdependent manner (Stratmann et al, 2000;Agrawal et al, 2003;Caputo et al, 2006;Foggo et al, 2007;Clarke et al, 2009;Demkura et al, 2010). All in all, these data suggest that UVinduced systemic recombination signal and SWS may share common signaling molecules.…”
Section: Online)mentioning
confidence: 74%
“…The strongest evidence for a role of JA in some defense responses triggered by natural doses of UV-B radiation comes from studies using mutants or transgenic lines impaired in JA biosynthesis or signaling. Disruption of the JA signaling pathway in Arabidopsis (Caputo et al, 2006) and Nicotiana attenuata (Demkura et al, 2010) was shown to eliminate the effect of solar UV-B inducing plant protection against herbivorous insects. In contrast, a recent case was reported in which a positive effect of UV-B radiation on plant resistance against pathogens was conserved in JA-response mutants , suggesting that UV-B radiation likely influences plant defense via multiple pathways.…”
Section: Uv-b and Uvr8mentioning
confidence: 99%